Faktor-faktor yang mempengaruhi kelengkapan vaksinasi dasar pada balita usia 9-24 bulan - Samino, Samino; Rahmandini, Hafizhah Harjiati; Lukman, Iing; Amirus, Khoidar; Riyanti, Riyanti (Holistik Jurnal Kesehatan, 2024)
Background: Basic vaccination is the first type of vaccination that must be given to babies from birth to protect their bodies from certain diseases. The vaccination program is part of an effort to reduce morbidity, morbidity and mortality in infants and toddlers. In 2019-2020, basic vaccination achieved 95% according to the target, and from mid-2020 to the end of 2021 it was only 76% and in 2022 there will be an increase of around 85%.Purpose: To determine the determinants of the completeness of basic vaccinations for toddlers aged 9-24 months at the UPTD of the Capable Poned Inpatient Health Center in Tulang Bawang Barat in 2023.Method: Quantitative analytical research with a cross-sectional design. The technique for taking the sample size was purposive sampling, and those who met the inclusion criteria were 108 people. Data analysis used the chi square test and multivariate analysis used multiple logistic regression.Results: Analysis shows that mothers have low education (51.9%), receive family support (54.6%), access to affordable vaccination services (75.9%), receive support from the role of health workers (63.9%). There is a significant relationship between education level (p–value=0.026), family support (p–value=0.000), accessibility of vaccination services (p–value= 0.000), support from the role of health workers (p–value=0.000) and completeness of vaccination base. Multivariate analysis of family support is the dominant variable in the completeness of basic vaccinations in children compared to the role of health workers and access to health services (p-value=0.000).Conclusion: The most dominant influencing factor on the completeness of basic vaccination is the family support factor compared to the mother's education factor, service access factor, and the support factor of the role of health workers.Suggestion: There is a need to increase outreach and education about the importance of basic vaccinations for the health and immunity of babies to avoid dangerous diseases, to increase knowledge among the public, especially mothers and their families, so they can understand the purpose and benefits of vaccination for the health of their toddlers. Keywords: Children; Vaccinations; Toddlers. Pendahuluan: Vaksinasi dasar merupakan jenis vaksinasi pertama yangg harus diberikan pada bayi sejak lahir untuk melindungi tubuhnya dari penyakit tertentu. Program vaksinasi termasuk dalam upaya untuk menurunkan angka kesakitan, kecatatan dan kematian pada bayi dan balita. Pada tahun 2019-2020 awal pencapaian vaksinasi dasar 95% sesuai target, dan pertengahan tahun 2020 sampai akhir tahun 2021 menjadi hanya 76% dan pada tahun 2022 mengalami kenaikan sekitar 85%.Tujuan: Untuk mengetahui determinan kelengkapan vaksinasi dasar pada balita usia 9-24 bulan di UPTD Puskesmas Rawat Inap Mampu Poned Dayamurni Tulang Bawang Barat tahun 2023.Metode: Penelitian analitik kuantitatif dengan rancangan Cross-Sectional. Teknik pengambilan jumlah sampel purposive  sampling, dan yang memenuhi kriteria inklusi sebanyak 108 orang. Analisa data menggunakan uji chi square dan analisa multivariat menggunakan regressi logistic ganda.Hasil: Analisis diperoleh bahwa ibu berpendidikan rendah (51.9%), mendapat dukungan keluarga (54.6%), aksesibilitas pelayanan vaksinasi yang terjangkau (75.9%), mendapatkan dukungan peran petugas kesehatan (63.9%). Ada hubungan yang signifikan antara tingkat pendidikan (p–value=0.026), dukungan keluarga (p–value=0.000), Aksesibilitas Pelayanan Vaksinasi (p–value= 0,000),dukungan peran petugas kesehatan(p–value=0,000) dengan kelengkapan vaksinasi dasar. Analisa multivariate dukungan keluarga merupakan variabel dominan terhadap kelengkapan vaksinasi dasar pada anak dibandingkan dengan peran petugas kesehatan dan akses pelayanan kesehatan ( p–value=0.000).Simpulan: Faktor berpengaruh yang paling dominan terhadap kelengkapan vaksinasi dasar adalah faktor dukungan keluarga dibandingkan dengan faktor pendidikan ibu, faktor akses pelayanan, dan faktor dukungan peran petugas kesehatan.Saran: Perlu ditingkatkan lagi penyuluhan dan edukasi tentang pentingnya vaksinasi dasar untuk kesehatan dan kekebalan tubuh bayi agar terhindar dari penyakit berbahaya, untuk meningkatkan pengetahuan kepada masyarakat khususnya ibu-ibu dan keluarganya sehingga bisa mengerti apa tujuan dan manfaat dari vaksinasi untuk kesehatan balitanya. Kata Kunci: Anak-anak; Balita; Vaksinasi Dasar.